2009
DOI: 10.1128/mcb.01262-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of SMN Protein Stability

Abstract: Spinal muscular atrophy (SMA) is caused by mutations of the survival of motor neuron (SMN1) gene and deficiency of full-length SMN protein (FL-SMN). All SMA patients retain one or more copies of the SMN2 gene, but the principal protein product of SMN2 lacks exon 7 (SMN⌬7) and is unable to compensate for a deficiency of FL-SMN. SMN is known to oligomerize and form a multimeric protein complex; however, the mechanisms regulating stability and degradation of FL-SMN and SMN⌬7 proteins have been largely unexplored.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
261
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(278 citation statements)
references
References 44 publications
11
261
0
2
Order By: Relevance
“…In humans, SMN2 is present in the same genomic region and differs from SMN1 by a single‐nucleotide substitution that results in the exclusion of exon 7 in approximately 90% of SMN transcripts 5, 6. The mRNA that results, SMNΔ7, produces a truncated protein that is nonfunctional and targeted for degradation 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…In humans, SMN2 is present in the same genomic region and differs from SMN1 by a single‐nucleotide substitution that results in the exclusion of exon 7 in approximately 90% of SMN transcripts 5, 6. The mRNA that results, SMNΔ7, produces a truncated protein that is nonfunctional and targeted for degradation 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…The two paralogs are nearly identical but differ by several key nucleotides within and flanking exon 7 (4). As a result, transcripts arising from the SMN2 locus predominantly splice out exon 7, producing a protein that is rapidly degraded and thought to be nonfunctional; however, a small fraction of transcripts include exon 7 and encode a protein identical to SMN1 (5). Importantly, SMN2 copy number varies across individuals and is a modifier of disease severity, with a higher copy number leading to reduced severity.…”
mentioning
confidence: 99%
“…SMN stability is affected by its ability to oligomerize. Therefore, SMN mutations that prevent oligomerization lead to rapid degradation, and this may be the reason that it causes SMA (Burnett et al, 2008). It is also worth mentioning that the SMN protein is part of a large multiprotein complex (the SMN complex), which is essential for the biogenesis of small nuclear ribonucleoprotein particles (snRNPs).…”
Section: Badr and Heathmentioning
confidence: 99%
“…It has been shown that ubiquitin has a controlling role in the splicing pathway and hence affects spliceosome assembly (Bellare et al, 2008). Moreover, according to Burnett et al (2008), ubiquitin influences the stability and degradation of the SMN protein. In humans, SMN is encoded by two genes, SMN1 and SMN2.…”
Section: Badr and Heathmentioning
confidence: 99%
See 1 more Smart Citation